Final answer:
To solve the system of linear equations -3x = -26 - 2y and -11x = .90 - 2y, we can use the method of substitution. The solution is x = (-5.1x - 2.6), y = (-5.1x - 2.6).
Step-by-step explanation:
To solve the system of linear equations -3x = -26 - 2y and -11x = .90 - 2y, we can use the method of substitution or elimination. Let's use the method of substitution:
- Solve one equation for one variable. Let's solve -3x = -26 - 2y for x: -3x = -26 - 2y ⟹ -3x + 2y = -26
- Substitute the expression found in step 1 into the other equation. Substitute -3x + 2y = -26 into -11x = .90 - 2y:
- -11x = .90 - 2y ⟹ -11x = .90 - 2y
- -11x = .90 - 2(-3x + 2y) ⟹ -11x = .90 + 6x - 4y
- -11x - 6x = .90 - 4y ⟹ -17x = .90 - 4y
- Solve the resulting equation for the remaining variable. Let's solve -17x = .90 - 4y for x: -17x = .90 - 4y ⟹ -17x + 4y = .90
- Substitute the value found in step 3 back into one of the original equations to find the remaining variable. Substitute -17x + 4y = .90 into -3x = -26 - 2y:
- -3x = -26 - 2y ⟹ -3(-17x + 4y) = -26 - 2y
- -3(-17x + 4y) = -26 - 2y ⟹ 51x - 12y = -26 - 2y
- 51x - 12y = -26 - 2y ⟹ 51x - 12y + 2y = -26
- 51x - 10y = -26
- Solve the resulting equation for the remaining variable. Let's solve 51x - 10y = -26 for y: 51x - 10y = -26 ⟹ -10y = -51x - 26 ⟹ -10y = 51x + 26
- Rewrite the equation in the form y = mx + b. Divide both sides of the equation by -10: y = -5.1x - 2.6
The solution to the system of linear equations is x = (-5.1x - 2.6), y = (-5.1x - 2.6).